Our Experience with the Low-Profile Braided Occluder: A Case Series of Splenic Artery Embolization in Three Trauma Patients - Christopher Stevens; Chintan Mehta; Dylan Scott; Chaitanya Ahuja; Massoud Allahyari (Indian Journal of Radiology and Imaging)
The spleen is the most injured intra-abdominal organ, with splenic injuries constituting 42 to 49% of all abdominal injuries. Due to this vulnerability and the fact that splenic ruptures can potentially result in life-threatening hemorrhage, finding quick and efficient ways to control splenic bleeding in a trauma setting can improve patient outcomes. Recently, the U.S. Food and Drug Administration cleared the low-profile braided occluder (LOBO; Okami Medical, Aliso Viejo, California, United States), a vascular occlusion system designed to rapidly occlude vessels by using a high-density, uniform small pore structure. We present a small case series describing the use of the LOBO device for proximal splenic embolization in three trauma patients. Our report suggests that the LOBO device is safe and efficient for proximal splenic artery embolization as all three of our patients had a successful outcome with no complications; furthermore, we believe using the LOBO device may enhance patient and provider safety by decreasing fluoroscopic time and radiation dose, though further studies are needed to support this.